KENAKALAN REMAJA DAN PERANAN GURU BK DALAM MENGATASINYA DI SMK MUHAMMADIYAH 1 PEKANBARU - Rahmadhani Dahlia; Elni Yakub; Zulfan Saam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The fact that at the present time is still a lot of juvenile delinquency among students therefore guidance and counseling teachers (BK) plays a very important role in dealing with the problem of juvenile delinquency in learners. Therefore, researchers feel the need to analyze about juvenile delinquency and the role of BK teachers in overcoming them. This study aims to determine the description of the types of juvenile delinquency and the role of BK teachers in overcoming juvenile delinquency. The subjects were 3 BK teachers.The method used is a quantitative approach. The research data was obtained through questionnaire. Analyze data using percentage techniques. The results showed that the description of the types of juvenile delinquency was in the low category. Juvenile delinquents include fights, coercion, bodily harm, destruction, theft, lack of self-esteem and honor, drug abuse, alcohol consumption, pornography, school treking, late daatang to school, no complete attributes to school, smoking in in school environments, cheating in the classroom and lying to teachers and friends.Misbehavior is in the low category because of the role of BK teacher in overcoming juvenile delinquency in good category. BK Teachers cope with juvenile delinquency by taking preventive actions such as conducting religious activities, extracurricular activities, providing motivation, orientation services, information services, group guidance, data collection services, media services. Curative action is to train discipline, orderly, and orderly, doing healthy recreation with high discipline, activating youth organization, counseling, follow-up and hand over case. Repressive measures of oral and written warnings, punishment, home visit and involving all components.Keywords: Juvenile delinquency, Role of teacher BK